FRA ANSTALT TIL SAMFUND – NYE VEJE FOR DOMFÆLDTE UNGE I GRØNLAND - Berliner, Peter (Psyke & Logos, 2015)
The development in prevention of recidivism in juvenile delinquents in Kalaallit Nunaat (Greenland) is presented and discussed. Rehabilitation through participation in shared prosocial activities in the local community has been the guiding principle of punishment in Kalaallit Nunaat over decades and is in a process of being strengthened through focused and expanded resources. The guiding principles are informed by Inuit traditions for maintaining social order in cases of anti-social behavior. Today this knowledge is transformed into an institutional response to the high, but slightly falling, rates of violence, sexual abuse and domestic violence. The prevention of recidivism encompasses opening opportunities to engage in the social life of the community through active participation in prosocial activities in work, education, sport and hunting. This requires cooperation of the local communities and the correction facility. This knowledge has been developed in Kalallit Nunaat, but can also contribute to the international knowledge on how to rehabilitate juvenile delinquents through a particular combination of social support in the community with an open institutional practice.